Childhood in the Middle Ages and the Renaissance The Results of a Paradigm Shift in the History of Mentality - Classen, Albrecht (De Gruyter, 2005)
Although many researchers have taken a critical stance towards the theses on the history of childhood developed by Philippe Ariès in 1960, this volume is the first comprehensive collection of studies with a psychological and emotional historical orientation to demonstrate convincingly the extent to which the relationship between parents and children was a fundamental element of European society in pre-modern times.